Personality traits and their effect on Facebook user habits - Johnson, Chance William Garrett, author; Plaisance, Patrick, advisor; Switzer, Jamie, committee member; Marx, Nick, committee member (Colorado State University. Libraries, 2016)
A survey, conducted in cooperation with faculty and staff at Colorado State University, was conducted with CSU undergraduates (n = 125) to explore how personality traits affect Facebook use and levels of self-disclosure among users. The intent was to explain why individuals partake in certain activities, and at what levels they engage in self-disclosure on Facebook based on their personality traits and gender. This study employed the Big Five Personality Test and the Narcissistic Personality Inventory in the first part of a survey to test the levels of the personality traits narcissism, extroversion, openness to experience, conscientiousness, agreeableness, and neuroticism. The second half of the survey asked a variety of questions listed as scaled items concerning Facebook activities having to do with self-disclosure, and at what levels the participants engage in each activity. While the personality traits observed were unable to predict the participants’ motivations for Facebook use and levels of self-disclosure in a statistically significant manner, this study confirmed that gender was a significant predictor of whether females or males engage in a certain activity more often, and at what level. These results were used to re-examine recommendations from past theoretical literature about how to predict Facebook behavior based on personality traits.
Zip file contains participant letter and survey.